BET 2: Is early chemical thromboprophylaxis safe in patients with blunt trauma solid organ injury (SOI) undergoing non-operative management (NOM)?. Issue 2 (19th January 2018) - Ferguson, Craig; Lewin, Jonathan
Abstract : A short cut review was carried out to establish whether chemical thromboprophylaxis was a safe early intervention in patients with solid organ injury that is being managed non-operatively. Eight papers presented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results and study weaknesses of these papers are tabulated. It is concluded that there is inadequate evidence assessing safety of low molecular weight heparin (LMWH) within 24 hours of trauma. The current available evidence does suggest that administration of LMWH within 48 hours is safe in non-operative management of patients who have sustained solid organ injury from blunt trauma.